E-HRM as a Mediator of the Relationship Between Work Competence and Work Motivation on Employee Performance - Purnomo, Joko (SENTRALISASI, 2024)
Employee performance has a very important role in determining the success of a company. When employee performance is at an optimal level, it can increase overall productivity, operational efficiency, and also the quality of goods and services offered by the company. This research aims to determine the role of e-HRM as a mediator in the relationship between competence and work motivation on employee performance in the garment industry in Central Java. The method applied in this research adopts a quantitative method with a qualitative approach to understand the behavioral and psychological aspects that influence employee performance. This research is cross-sectional. Data is collected through surveys via questionnaires which will be distributed to employees and literature studies. Samples were taken using the Accidental Sampling technique to obtain 50 samples. The data that has been collected is then analyzed using a regression test. The research results show that in the garment industry in Central Java, competency and work motivation have a positive and significant effect on employee performance. E-HRM is able to encourage employee performance through work competency and work motivation. E-HRM can help companies improve employee work competency by providing training and development that is relevant to job needs. E-HRM can also help companies increase employee motivation by providing programs that can meet employee needs.